Assembly of Ebola virus matrix protein VP40 is regulated by latch-like properties of N and C terminal tails. - Leslie P Silva (Public Library of Science (PLoS), 2012)
The matrix protein VP40 coordinates numerous functions in the viral life cycle of the Ebola virus. These range from the regulation of viral transcription to morphogenesis, packaging and budding of mature virions. Similar to the matrix proteins of other nonsegmented, negative-strand RNA viruses, VP40 proceeds through intermediate states of assembly (e.g. octamers) but it remains unclear how these intermediates are coordinated with the various stages of the life cycle. In this study, we investigate the molecular basis of synchronization as governed by VP40. Hydrogen/deuterium exchange mass spectrometry was used to follow induced structural and conformational changes in VP40. Together with computational modeling, we demonstrate that both extreme N and C terminal tail regions stabilize the monomeric state through a direct association. The tails appear to function as a latch, released upon a specific molecular trigger such as RNA ligation. We propose that triggered release of the tails permits the coordination of late-stage events in the viral life cycle, at the inner membrane of the host cell. Specifically, N-tail release exposes the L-domain motifs PTAP/PPEY to the transport and budding complexes, whereas triggered C-tail release could improve association with the site of budding.